Therapeutic utility of glucocorticoids and antihistamines cotreatment. Rationale and perspectives - Carlos D. Zappia; Federico Monczor (Wiley, 2019)
Abstract Antihistamines and glucocorticoids (GCs) are often used together in the clinic, in several inflammatory‐related situations. Even though there is no clear rationale for this drug association, the clinical practice is based on the assumption that due to their concomitant antiinflammatory effects, there should be an intrinsic benefit in their coadministration. Our group has studied the molecular interaction between the histamine H1 receptor and the glucocorticoid receptor (GR) signaling pathways, showing an enhancing effect on GC‐induced GR transcriptional activity induced by antihistamines. We hypothesize that the existence of this synergistic effect could contribute in reducing the GCs clinical doses, ineffective by itself but effective in combination with an antihistamine. This could result in a therapeutic advantage as the GC‐desired effects may be reinforced by the addition of an antihistamine and, as a consequence of the dose reduction, GC‐related adverse effects could be reduced or at least mitigated. Here we discuss the potential therapeutic applications of this cotreatment seeking to evaluate its usefulness, especially in inflammatory‐related conditions.